Prediction model for long-term seizure and developmental outcomes among children with infantile epileptic spasms syndrome - Arai, Yuto; Okanishi, Tohru; Kanai, Sotaro; Nakamura, Yuko; Sunada, Hiroshi; Murakami, Hinata; Yamauchi, Kazuki; Noma, Hisashi; Maegaki, Yoshihiro (Frontiers in Neurology, 2023)
Introduction Children with infantile epileptic spasms syndrome (IESS) are likely to experience poor outcomes. Researchers have investigated the factors related to its long-term prognosis; however, none of them developed a predictive model. Objective This study aimed to clarify the factors that influence the long-term prognosis of seizures and their development and to create a prediction model for IESS. Materials and methods We conducted a retrospective cohort study enrolling participants diagnosed with IESS at the Tottori University Hospital. We examined the seizure and developmental status at 3 and 7 years after the IESS onset and divided the participants into favorable and poor outcome groups. Subsequently, we analyzed the factors associated with the poor outcome group and developed a prediction model at 3 years by setting cutoff values using the receiver operating characteristic curve. Results Data were obtained from 44 patients with IESS (19 female patients and 25 male patients). Three years after epileptic spasms (ES) onset, seizure and development were the poor outcomes in 15 (34.9%) and 27 (61.4%) patients, respectively. The persistence of ES or tonic seizures (TS) after 90 days of onset, moderate or severe magnetic resonance imaging abnormalities, and developmental delay before IESS onset were significantly associated with poor outcomes. Seven years after the onset of ES, seizures and development were the poor outcomes in 9 (45.0%) and 13 (72.2%) patients, respectively. We found that no factor was significantly associated with poor seizure outcomes, and only developmental delay before IESS onset was significantly associated with poor developmental outcomes. Our prediction model demonstrated 86.7% sensitivity and 64.3% specificity for predicting poor seizure outcomes and 88.9% sensitivity and 100% specificity for predicting poor developmental outcomes. Conclusion Our prediction model may be useful for predicting the long-term prognosis of seizures and their development after 3 years. Understanding the long-term prognosis during the initial treatment may facilitate the selection of appropriate treatment.